2012
DOI: 10.1186/1472-6882-12-129
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of complementary and alternative medicine use among infertile patients in Lebanon: a cross sectional study

Abstract: BackgroundComplementary and alternative medicine (CAM) is widely used for the treatment of infertility. While the Middle East and North Africa region has been shown to house one of the fastest growing markets of CAM products in the world, research describing the use of CAM therapies among Middle-Eastern infertile patients is minimal. The aim of this study is to examine the prevalence, characteristics and determinants of CAM use among infertile patients in Lebanon.MethodsA cross sectional survey design was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
50
3
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 24 publications
9
50
3
11
Order By: Relevance
“…In addition, only 6.9% informed their physician of such use, despite the fact that patient were recruited from physician’s clinics. Other studies revealed a similar or even lower pattern of reporting [35,36,45-48]. These findings suggest that health care practitioners played a marginal role in regards to their patients’ use of CAM therapies and that they remain largely blinded to their patients’ use of CAM despite the fact that some patients are using CAM on an alternative basis to current treatment.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, only 6.9% informed their physician of such use, despite the fact that patient were recruited from physician’s clinics. Other studies revealed a similar or even lower pattern of reporting [35,36,45-48]. These findings suggest that health care practitioners played a marginal role in regards to their patients’ use of CAM therapies and that they remain largely blinded to their patients’ use of CAM despite the fact that some patients are using CAM on an alternative basis to current treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Since ancient times, medicinal plants have been proposed for the treatment of various disorders including infertility. Different prevalence of use of medicinal plants among infertile couples has been reported, including 21% in Jordan (Bardaweel et al., ), 17% in the United States (Smith et al., ) and 12.2% in Lebanon (Ghazeeri et al., ). In this article, electronic databases were searched to find any evidence about the efficacy of medicinal plants used in traditional Persian medicine for treatment of male infertility related to abnormal sperm parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reports of its antifertility and antiandrogenic capacities in male rabbits, rats and mice (Kamal et al 1993;Kassem et al 2006;Al-Janabi 2011), fenugreek exerted reversal of lindane-associated reactive oxygen species (ROS)-damage in male rat's reproductive and accessory organs with restoration of fertility, testosterone levels and amelioration of functionality (Seshadri et al 2011). On the other hand, N. sativa oil is promoted as a male fertility agent (Ghazeeri et al 2012) and could ameliorate and reverse the nicotine-induced reduction in sperm motility and morphology and affected testicular histology (Cho Ping et al 2014). It was also found to improve hyperlipidemic male rat fertility and spermatogenesis (Bashandy 2007;Al-Saaidi et al 2009;Mohammad et al 2009;Parandin et al 2012;Mansour et al 2013;Marbat et al 2013).…”
Section: Herbal Remedies Of Male Fertility/infertility Issuesmentioning
confidence: 99%
“…Thymoquinone treatment during pregnancy in diabetic mice inhibited embryo malformations and increased the size and maturation of embryos (Al-Enazi 2007). Black seed oil is promoted as male fertility agent (Ghazeeri et al 2012) and could ameliorate and reverse the nicotine induced reduction in sperm motility and morphology and Antidiabetic, hypotensive, antiobesity, antiinflammatory, antioxidative, cytotoxic-proapoptotic, hypolipidemic, nephroprotective, antiepileptic with antimalarial and antifungal capacities (Develi et al 2014;Razavi & Hosseinzadeh 2014;Afifi & Kasabri 2014;Tembhurne et al 2014). Vasorelaxant in rat aorta (Niazmand et al 2014) and antidepressant (Perveen et al 2013).…”
Section: Herbal Remedies With Female Antifertility and Abortificiant mentioning
confidence: 99%